Potential of zinc seed treatment in improving stand establishment, phenology, yield and grain biofortification of wheat. (27th August 2019) - Hassan, Nazia; Irshad, Sohail; Saddiq, Muhammad Sohail; Bashir, Saqib; Khan, Shahbaz; Wahid, Muhammad Ashfaq; Khan, Rashad Rasool; Yousra, Munazza
Abstract: One of the problems in obtaining high wheat yield is the unavailability of micronutrients in balanced quantities. Zinc is an essential micronutrient due to its involvement in many metabolic processes in plant. In this experiment, seeds of two wheat cultivars (Faisalabad-2008 and Lasani-2008) were subjected to soak in aerated Zn solution of 0.1 and 0.01 M for 12 hr. For the seed coating, Zn was adhered to the wheat seeds by using Arabic gum by using zinc sulfate (ZnSO4 ·7H2 O) as a source. Untreated dry seeds were considered as a control. Results indicated that field emergence was improved by Zn seed treatments, maximum numbers of seedlings were observed in seed priming with 0.01 M Zn solution. Seed osmoprimed with 0.01 M Zn solution improved the grain yield, biological yield, and other yield related traits. Grain and straw Zn enrichment were also enhanced in seed osmoprimed with 0.01 M Zn solution.